VISUAL ANTHROPOLOGICAL STUDY OF PHOTOGRAPHIC WORKS OF GUNUNG PADANG SITE AS A TOURIST ATTRACTION IN KARYAMUKTI VILLAGE, CIANJUR, WEST JAVA - Winny Gunarti Widya Wardani; Wulandari Wulandari; Syahid Syahid (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
The results of the Ancient Catastropic Team's research on the Gunung Padang Site in Karyamukti Village, Cianjur, West Java, in 2011 showed that the site was older than the Giza Pyramid in Egypt. The jumble of stones in the hilly area of ​​the site is authentic evidence of the archeology of the Megalithic era. Prehistoric relics in this region are important because of the unique cultural values ​​that are part of the principles of local tourism development in Indonesia. The potential of historical and cultural tourism is also inseparable from the participation of the local community. Therefore, knowledge about the cultural values ​​of an area needs to be effectively disseminated through information media. This study aims to help preserve prehistoric relics through photography as a medium of visual communication. The combination method is used to analyze the attractiveness of the Gunung Padang Site as a potential tourist destination. Quantitatively, survey data show that 61 percent of people are interested in visiting the Gunung Padang Site because they want to know the background of prehistoric stones and take pictures with the natural scenery. Whereas qualitatively, the attraction of visual objects is described using a visual anthropology approach which is studying a culture through photography and the relationships associated with it. This study uses the principle of composition of the rule of thirds to present prehistoric stones on the Gunung Padang Site as images that carries a cultural message. The results of the analysis show that the photographic works that are focused on visualizing five stone structures as gates or entrances, streets and stairs, walls, spaces, and wells as a source of life can convey messages about the work of humans in building a place of worship to ancestral spirits as a civilization in the past. This study can be a reference in the field of visual communication design science about the Gunung Padang Site and is expected to help encourage public awareness to respect cultural heritage, as well as develop the tourism potential of the region.